Robust H? Filter Design for Singular Systems with Time-Varying Uncertainties - Acosta-Barbosa, K (2011)
This article deals with the design of robust H? filter for singular systems in general form, subject to bounded time-varying uncertainties. The aim is to design linear admissible descriptor filters that ensure a guaranteed bound on the L2 gain of the operator from the noise signals to the estimation error signal, irrespective of the time-varying uncertain parameters. A strict linear matrix inequality based method is proposed to the robust H? filter design employing affine Lyapunov functions. A numerical example is presented to show the efficiency of the proposed method. © 2011 The Institution of Engineering and Technology.